2008
DOI: 10.1111/j.1600-0463.2008.01017.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytolethal distending toxin upregulates RANKL expression in Jurkat T‐cells

Abstract: Cytolethal distending toxin, a bacterial exotoxin produced by a number of Gram-negative species, causes growth arrest and morphological alterations in host cells. Among these species are Haemophilus ducreyi, the etiological agent of chancroid, and the periodontal pathogen Aggregatibacter actinomycetemcomitans, highly implicated in localized aggressive periodontitis. CDT induces receptor activator of NF-kappaB ligand (RANKL) expression in periodontal fibroblasts, the key bone-resorbing cytokine. T-cells are act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 40 publications
0
21
1
1
Order By: Relevance
“…Our results differed from those of Belibasakis et al [83,84]. However, the toxin may induce the fibroblasts to release pro-inflammatory cytokines such as IL-6 and mediators of bone resorption such as RANKL in Stage II as shown by that group in in vitro studies [57]. …”
Section: Breakdown Of the Gingival Epithelial Barriercontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results differed from those of Belibasakis et al [83,84]. However, the toxin may induce the fibroblasts to release pro-inflammatory cytokines such as IL-6 and mediators of bone resorption such as RANKL in Stage II as shown by that group in in vitro studies [57]. …”
Section: Breakdown Of the Gingival Epithelial Barriercontrasting
confidence: 99%
“…This increase in expression was not attributed to a specific product but the Cdt is a reasonable candidate. RANKL was also up-regulated in response to the Hd Cdt in a T-lymphocyte leukemia cell line (Jurkat) [57]. RANKL is a member of the TNF ligand superfamily and binds to its associated receptor RANK on osteoclast progenitor cells [58].…”
Section: Aggregatibacter Actinomycetemcomitans Cdt Structure and Fmentioning
confidence: 99%
“…However, OPG expression was not detected in these cells and P. gingivalis challenge was not able to induce its expression. The lack of capacity by Jurkat T-cells to express OPG even in response bacterial challenge has previously been demonstrated [28], although it has also been reported that normal CD4+ T-cells can produce OPG [29]. This is an interesting point, as T-cell infiltrates in active periodontal lesions could stimulate bone resportion via RANKL, but it is not clear if they would be able to restore the physiological balance by compensatory OPG production that would inhibit osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, the ratio of RANKL/OPG expression determines the amount of osteoclasts formed and controls the degree of bone reabsorption. It has been shown that AactCDT is sufficient to induce RANKL expression and downregulate OPG mRNA expression in gingival fibroblasts and periodontal ligament cells, obtained from healthy individuals, and in the T lymphocyte cell line Jurkat [198,199]. Finally, by blocking proliferation and inducing apoptosis of activated human CD8 + and CD4 + T lymphocytes [132,[144][145][146], AactCDT may create an immune privilege niche suitable for bacterial survival, proliferation, and spreading.…”
Section: Periodontitismentioning
confidence: 98%